2017
DOI: 10.3382/ps/pew367
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Propionibacterium freudenreichii on Salmonella multiplication, motility, and association with avian epithelial cells

Abstract: We investigated the effects of a probiotic bacterium, Propionibacterium freudenreichii, on Salmonella multiplication, motility, and association to and invasion of avian epithelial cells in vitro. Two subspecies of P. freudenreichii (P. freudenreichii subsp. freudenreichii and P. freudenreichii subsp. shermanii) were tested against 3 Salmonella serotypes in poultry, namely, S. Enteritidis, S. Typhimurium, and S. Heidelberg, using co-culture-, motility, multiplication, cell association, and invasion assays. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…Heidelberg. A study conducted by Nair and Kollanoor-Johny [ 162 ] revealed that probiotic P. freudenreichii isolated from fermented dairy products was effective against major virulence factors of multidrug-resistant S. Heidelberg. Compared to the antibiotic-resistant parent strains, probiotic-treated S. Heidelberg showed reduced multiplication, motility, and adhesion on intestinal epithelial cells.…”
Section: Ongoing Studies With Alternative Interventions Against Mumentioning
confidence: 99%
“…Heidelberg. A study conducted by Nair and Kollanoor-Johny [ 162 ] revealed that probiotic P. freudenreichii isolated from fermented dairy products was effective against major virulence factors of multidrug-resistant S. Heidelberg. Compared to the antibiotic-resistant parent strains, probiotic-treated S. Heidelberg showed reduced multiplication, motility, and adhesion on intestinal epithelial cells.…”
Section: Ongoing Studies With Alternative Interventions Against Mumentioning
confidence: 99%
“…The pellet was resuspended in 10 ml of PBS, and the bacterial populations in the culture were confirmed by plating 0.1 ml of appropriate dilutions on MRS plates. Viable PF and PS populations were determined after incubating the plates at 41°C (turkey body temperature) for 48 h ( Nair and Kollanoor-Johny, 2017a ).…”
Section: Methodsmentioning
confidence: 99%
“…A US poultry outbreak isolate of MDR SH was used in the study (GT2011; Nair and Kollanoor-Johny, 2017a , b ; Nair et al, 2018 ). Glycerol stocks of SH stored at −80°C were used for the preparation of working cultures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Propionibacteria adhesion to intestinal cells leads to exclusion of invasive pathogenic bacteria by competitive adhesion or co-aggregation mechanisms. This concerns pathogens such as Escherichia coli , Pseudomonas aeruginosa , S taphylococcus aureus and Salmonella enterica [41,42,43,44]. Adhesion mechanisms remain poorly understood, but some preliminary experiments point out a role of surface proteins and teichoic acid in adhesion mechanisms [37].…”
Section: Gut Persistence Of Dairy Propionibacteriamentioning
confidence: 99%